An Islamic Legal Study on the Practice of Tubectomy Contraception in Palimanan District, Cirebon Regency - Fadhlu Humaedillah Nur (Media Hukum Indonesia (MHI), 2026)
This study aims to describe and analyze the practice of tubal ligation contraception in Palimanan District, Cirebon Regency, as well as to analyze Islamic law perspectives on this practice. Tubal ligation as a permanent contraceptive method raises debate among scholars because it relates to maqÄá¹£id al-syarÄ«'ah, especially in the aspect of á¸¥ifáº“ al-nasl (preserving lineage). This research uses qualitative methods with a descriptive-analytical approach. Data were collected through in-depth interviews with tubal ligation acceptors, health workers, religious leaders, and Family Planning program officers. Data analysis was conducted using maqÄá¹£id al-syarÄ«'ah theory and maá¹£laá¸¥ah principles. The results show that the practice of tubal ligation in Palimanan District is carried out for various reasons, including: economic factors, health reasons, medical personnel recommendations, and government programs. Most acceptors do not deeply understand the position of Islamic law regarding tubal ligation. From an Islamic law perspective, tubal ligation is categorized as a permanent contraception that is basically not recommended except in emergency conditions (á¸arÅ«rah) that meet shar'i criteria, such as threats to the mother's life. This study recommends the importance of comprehensive Islamic law education before performing tubal ligation, active involvement of religious leaders in Family Planning programs, and strengthening the principle of informed consent based on Islamic values.